Evaluation of tooth eruption rate of incisor teeth in rats with estrogen deficiency - Madalena, Isabela Ribeiro; Marañón-Vásquez, Guido Artemio; Omori, Marjorie Ayumi; de Sousa, Emerson Tavares; da Silveira, Heitor Albergoni [UNESP]; León, Jorge Esquiche; Baratto-Filho, Flares; Alves, Sandra Yasuyo Fukada; Stuani, Maria Bernadete Sasso; Nelson-Filho, Paulo; Kirschneck, Christian; Küchler, Erika Calvano (Springer Nature, 2023)
Objectives: To assess the influence of estrogen deficiency on tooth eruption rate (TER) and gene expression of estrogen receptor alpha and beta (ERα and ERβ) in the odontogenic region of teeth with continuous formation in a rat model. Materials and methods: Ovariectomies (OVX; n = 25) and sham surgeries (SHAM; n = 25) were performed in female Wistar rats when animals were 25 days old. The TER of the lower incisors, both in impeded (hyperfunction condition) and unimpeded (trimmed incisal edge—hypofunction condition) conditions, was evaluated using standardized digital photographs acquired every 48–72 h for 3 weeks (35th–53rd day of life), using a camera coupled to a stereomicroscope. Quantitative real-time PCR was performed to evaluate the relative gene expression of ERα and ERβ in the odontogenic region. Results: The OVX group showed a significant reduction in TER when compared to the SHAM group, only in the impeded condition (p = 0.03). There was no statistically significant difference between the groups in ERα gene expression (p = 0.33). ERβ showed a significantly higher gene expression in the OVX group (p ≤ 0.05). Conclusions: Estrogen deficiency decreases TER in teeth under impeded condition. Estrogen deficiency also increases ERβ gene expression in the odontogenic region of teeth with continuous formation. Clinical relevance: Hormonal disturbances affecting estrogen levels can cause alterations in dental formation and teeth eruption.
Keywords: Estrogen receptor alpha; Estrogen receptor beta; Estrogens; Odontogenesis; Tooth eruption